2018
DOI: 10.1186/s12967-018-1381-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases, inflammation, and spices: how are they linked?

Abstract: Extensive research within the last several decades has revealed that the major risk factors for most chronic diseases are infections, obesity, alcohol, tobacco, radiation, environmental pollutants, and diet. It is now well established that these factors induce chronic diseases through induction of inflammation. However, inflammation could be either acute or chronic. Acute inflammation persists for a short duration and is the host defense against infections and allergens, whereas the chronic inflammation persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
211
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(220 citation statements)
references
References 300 publications
(167 reference statements)
4
211
0
5
Order By: Relevance
“…This data allows us to hypothesize that the presence of chronic diseases not only increases the risk of complicated disease but even the risk of acquiring the novel coronavirus. A possible explanation is that chronic in ammation, negative effects on immunomodulation and metabolic stress that characterized systemic diseases decrease the ability to react against external agents; in this case, SARS-CoV-2 (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…This data allows us to hypothesize that the presence of chronic diseases not only increases the risk of complicated disease but even the risk of acquiring the novel coronavirus. A possible explanation is that chronic in ammation, negative effects on immunomodulation and metabolic stress that characterized systemic diseases decrease the ability to react against external agents; in this case, SARS-CoV-2 (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal inflammation was the most common condition investigated, using Caco-2 and HT29 cells. Both are well characterized epithelial cell lines, derived from a primary colon tumor; thanks to their similarities with enterocytes of the human small intestine, they are a suitable model to study effects/absorption of food substances [12][13][14][15]. Nicod and co-workers [15] and Nunes and co-workers [16,17] evaluated the effects of wine polyphenols on inflammatory biomarkers production by CaCo-2 and HT-29 cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The dysregulation of various signaling pathways, such as the nuclear factor kappa-B (NF-κB) and signal transducer and activator of transcription 3 (STAT3), seems to be involved in inflammation. In fact, these factors regulate the transcription of specific enzymes, such as cycloxigenase-2 (COX-2), matrix metalloproteinase-9 (MMP-9), and inflammatory cytokines (tumor necrosis factor alpha (TNF-α), interleukin-1, -6, -8, (IL-1, IL-6, IL-8), and chemokines) [12]. The relationship between inflammation and chronic diseases has been suggested by different papers [11,13], as well as the possible positive role of wine in this process by in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that exact management of chronic diseases is only possible when we will have in depth scientific investigation i.e., natural derived bioactive compounds, structure elucidation, understanding molecular pathways of disease etc [15].…”
Section: Translational Molecular Sciencementioning
confidence: 99%